Knowledge management for small-scale agricultural producers: a thematic proposal for strengthening rural economic units (Agro Productividad, 2024)
Objective: To establish a thematic proposal for the management of knowledge of small-scale agricultural producers (peasants) and the strengthening of rural economic units in the state of Querétaro, to energize the social fabric and improve the quality of life of the rural population.Design/methodology/approach: A bibliometric study of the scientific production on peasant knowledge in Mexico was carried out, as well as an observational analysis focused on specific and general problems. According to the information obtained and the problems detected, three areas for knowledge management were established: technical-productive, managerial and entrepreneurial.Results: In the technical-productive area, training in good agricultural practices should be addressed, along with technological innovation and the generation of added value. In the management area, issues related with strategic management with a broad entrepreneurial vision that could help create strategies for agribusiness development. Concerning entrepreneurship, the internal and external factors of the environment stand out, which allow awakening their interest, encouraging leadership and direction for business development, in addition to promoting associativity in farming regions. The implementation of the topics proposed in the research will strengthen and boost small-scale agricultural production in the state of Querétaro.Limitations on study/implications: This study can serve as a reference for small-scale agricultural producers (peasant).Findings/conclusions: There is a great opportunity through knowledge management to increase the capacities, knowledge and skills of small-scale agricultural producers (peasants) in the state of Querétaro regarding technical-productive, managerial and entrepreneurial themes, which will generate economic, social and environmental impacts for the benefit of this rural sector.